Colanic Acid Is a Novel Phage Receptor of Pectobacterium carotovorum subsp. carotovorum Phage POP72 - Kim, Hyeongsoon; Kim, Minsik; Bai, Jaewoo; Lim, Jeong-A; Heu, Sunggi; Ryu, Sangryeol (Frontiers in Microbiology, 2019)
The emergence and widespread nature of pathogen resistance to antibiotics and chemicals has led to the re-consideration of bacteriophages as an alternative biocontrol agent in several fields, including agriculture. In this study, we isolated and characterized a novel bacteriophage, POP72, that specifically infects Pectobacterium carotovorum subsp. carotovorum (Pcc), which frequently macerates agricultural crops. POP72 contains a 44,760 bp double-stranded DNA genome and belongs to the family Podoviridae. To determine the phage receptor for POP72, a random mutant library of Pcc was constructed using a Tn5 transposon and screened for resistance against POP72 infection. Most of the resistant clones had a Tn5 insertion in various genes associated with colanic acid (CA) biosynthesis. The phage adsorption rate and CA production decreased dramatically in the resistant clones. Complementation of the clones with the pUHE21-2 lacIq vector harboring genes associated with CA biosynthesis restored their sensitivity to POP72, as well as their ability to produce CA. These results suggest that CA functions as a novel phage receptor for POP72. The application of POP72 protected Chinese cabbage from Pcc infection, suggesting that phage POP72 would be an effective alternative antimicrobial agent to protect agricultural products from Pcc.